2008
DOI: 10.1088/0022-3727/41/3/035302
|View full text |Cite
|
Sign up to set email alerts
|

Results on the electrochromic and photocatalytic properties of vanadium doped tungsten oxide thin films prepared by reactive dc magnetron sputtering technique

Abstract: In this investigation, vanadium doped tungsten oxide (V : WO3) thin films are prepared at room temperature by reactive dc magnetron sputtering employing a tungsten–vanadium ‘inlay’ target. In comparison with pure sputtered tungsten oxide thin films, 11% vanadium doping is observed to decrease the optical band gap, enhance the colour neutral property, decrease the coloration efficiency (from 121 to 13 cm2 C−1), increase the surface work function (4.68–4.83 eV) and significantly enhance the photocatalytic effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…The CVs obtained appear very similar to those observed with well-defined electrochromic WO 3 films as already reported in literatures [16,17,43,52]. The overall features of the CVs are in agreement with the results reported for WO 3 films deposited by other techniques in a H 2 SO 4 medium [13,15,17]. It is reported that as the classical amorphous WO 3 films have a broad distribution of energetically different intercalation sites, its cyclic voltammograms do not display sharp current peaks for neither reduction (intercalation) nor oxidation (deintercalation) [53,54].…”
Section: Cyclic Voltammetrysupporting
confidence: 90%
See 4 more Smart Citations
“…The CVs obtained appear very similar to those observed with well-defined electrochromic WO 3 films as already reported in literatures [16,17,43,52]. The overall features of the CVs are in agreement with the results reported for WO 3 films deposited by other techniques in a H 2 SO 4 medium [13,15,17]. It is reported that as the classical amorphous WO 3 films have a broad distribution of energetically different intercalation sites, its cyclic voltammograms do not display sharp current peaks for neither reduction (intercalation) nor oxidation (deintercalation) [53,54].…”
Section: Cyclic Voltammetrysupporting
confidence: 90%
“…No peaks were found corresponding to the stretching modes of V 3 -O (520 cm -1 ), V 2 -O (650 cm -1 ) and V 5+ = O (1027 cm -1 ) [13].…”
Section: Raman Studiesmentioning
confidence: 89%
See 3 more Smart Citations